COMPARATIVE STUDY OF BALADI GHRITA NASYA WITH GOGHRITA NASYA IN THE MANAGEMENT OF NASAPRATINAHA (International Journal of Ayurveda and Pharma Research, 2015)
Aim: To compare the effect of Baladi Ghrita Nasya with Goghrita Nasya in the management of Nasapratinaha.Objective: 1. To evaluate the effect of Baladi Ghrita (trail drug) Nasya in management of Nasapratinaha.2. To evaluate the effect of Nasya with Goghrita (control drug) in management of Nasapratinaha.Method: Patients were divided into 2 groups. i.e., Group A and Group B.Group A - Baladi Ghrita Nasya was administered for seven days, once daily in the morning.Group B- Nasya with Goghrita for seven days was administered, once daily in the morning.Types of study: Comparative Clinical Study.Period of Study: After seven days of treatment, both the groups were followed at regular intervals of 15 days for a period of two months.Follow Up: Both the groups were followed at regular intervals of 15 days.Results: By comparing both the groups, Group A patients those who were administered Baladi Ghrita Nasya showed a significant improvement / relief in the management of Nasapratinaha. Statistical Analysis: The Statistical Analysis reveals that In Nasapratinaha the efficacy of treatment with Baladi Ghrita Nasya has an effective role in treating Nasapratinaha than Nasya with plain Goghrita.Conclusion: In Nasapratinaha the efficacy of treatment with Baladi Ghrita Nasya has an effective role in treating Nasapratinaha than Nasya with plain Goghrita.